(untitled) (Medico Legal Update, 2021)
Introduction: Back pain and spinal deformity are common presentation in majority of senile osteoporotic vertebral compression fracture. Vertebroplasty provides pain relief with correction of spinal deformity and least period of hospital stay. Material and Method: Twenty patients underwent vertebroplasty and clinical evaluation of pain was done by recording the VAS score done preoperatively and after surgery. Result: Percutaneous vertebroplasty with 1 year followup.VAS score 52% were excellent,14% good and 34% fair result. Conclusion: Vertebroplasty is useful in management of vertebral compression fracture which are refractory to conservative treatment & helps in early mobilization.